1997
DOI: 10.1136/hrt.78.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Junctional ectopic tachycardia in six paediatric patients

Abstract: The presenting features and treatment responses of six children with junctional ectopic tachycardia are evaluated. Two of the patients were siblings and both presented in early childhood with cardiopulmonary failure. The elder sibling died, the surviving sibling was controlled on a combination of amiodarone, digoxin, and sotalol. The remaining four patients presented in later childhood with tachycardia induced cardiomyopathy. Two of the patients were diagnosed incidentally and have normalised their myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Many patients required Ͼ2 medications, either sequentially or in combination, to eventually see a salutary drug effect on JET rate. As in prior studies, our findings support the use of amiodarone for the treatment of JET (3,5). For patients for whom medications were thought to be effective for tachycardia conversion or rate control, amiodarone was the most frequently cited medication.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Many patients required Ͼ2 medications, either sequentially or in combination, to eventually see a salutary drug effect on JET rate. As in prior studies, our findings support the use of amiodarone for the treatment of JET (3,5). For patients for whom medications were thought to be effective for tachycardia conversion or rate control, amiodarone was the most frequently cited medication.…”
Section: Discussionsupporting
confidence: 86%
“…The mortality rate for JET has been previously reported by Villain et al (5) to be 34%, with 2 of 9 being sudden unexplained deaths in infants thought to have the JET rate controlled with medications. In contrast, Cilliers et al (3) showed no deaths among 9 patients with JET. In our population, we report a 4% mortality; all deaths occurred among patients presenting at age Յ6 months.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[78] However, there has been limited efficacy in restoring sinus rhythm. In extreme cases where pharmacologic therapy was unsuccessful in rate control, radio-frequency catheter ablation has been performed; however, this is often complicated by complete AV block and requires pacemaker implantation.…”
Section: Treatment Of Jetmentioning
confidence: 99%